Endosulfan use and the risk of thyroid cancer: an ecological study. Issue 1 (2nd January 2023) - Vasan, Vikram; Alsen, Mathilda; Vujovic, Dragan; Genden, Eric; Sinclair, Catherine; van Gerwen, Maaike
Abstract: Endosulfan, an organochlorine pesticide, has been understudied in the literature on thyroid cancer. The aim of this ecological study was to assess the correlation between endosulfan exposure and thyroid cancer incidence rates (IRs) in the United States (US). Age-adjusted thyroid cancer IRs per 100, 000 people per state for the years 1999 to 2019 were obtained from the Center for Disease Control and Prevention (CDC). To assess the state-level use of endosulfan, data were obtained from the US Geological Survey (USGS). Endosulfan usage estimates (kilograms/acres cropland; quintiles) and thyroid cancer IRs were mapped together. The correlation between age-adjusted thyroid cancer IRs and statewide endosulfan use was calculated using the Spearman correlation. Overall endosulfan usage in the US trended downwards between 1992 and 2007 ( T = −0.77; P < 0.001), while thyroid cancer IR trended upwards between 1999 and 2019 ( T = 0.69; P < 0.001). There was a statistically significant correlation between 1992 endosulfan use and 2012 ( r = 0.32; P = 0.03) and 2014 ( r = 0.32; P = 0.03) thyroid cancer IRs. Although restrictions on endosulfan use seem effective, the potential impact of endosulfan exposure remains due to the persistent, semi-volatile, bioaccumulative, and biomagnifying properties of endosulfan metabolites in particular, indicating the need for future thyroid research of highly exposed populations.